Chitosan crosslinked flat scaffolds for peripheral nerve regeneration. (10th August 2016) - Fregnan, F; Ciglieri, E; Tos, P; Crosio, A; Ciardelli, G; Ruini, F; Tonda-Turo, C; Geuna, S; Raimondo, S
Abstract: Chitosan (CS) has been widely used in a variety of biomedical applications, including peripheral nerve repair, due to its excellent biocompatibility, biodegradability, readily availability and antibacterial activity. In this study, CS flat membranes, crosslinked with dibasic sodium phosphate (DSP) alone (CS/DSP) or in association with the γ -glycidoxypropyltrimethoxysilane (CS/GPTMS_DSP), were fabricated with a solvent casting technique. The constituent ratio of crosslinking agents and CS were previously selected to obtain a composite material having both adequate mechanical properties and high biocompatibility. In vitro cytotoxicity tests showed that both CS membranes allowed cell survival and proliferation. Moreover, CS/GPTMS_DSP membranes promoted cell adhesion, induced Schwann cell-like morphology and supported neurite outgrowth from dorsal root ganglia explants. Preliminary in vivo tests carried out on both types of nerve scaffolds (CS/DSP and CS/GPTMS_DSP membranes) demonstrated their potential for: (i) protecting, as a membrane, the site of nerve crush or repair by end-to-end surgery and avoiding post-operative nerve adhesion; (ii) bridging, as a conduit, the two nerve stumps after a severe peripheral nerve lesion with substance loss. A 1 cm gap on rat median nerve was repaired using CS/DSP and CS/GPTMS_DSP conduits to further investigate their ability to induce nerve regeneration in vivo . CS/GPTMS_DSP tubes resulted to be more fragile during suturing and, along a 12 week post-operative lapse of time, they detached from the distal nerve stump. On the contrary CS/DSP conduits promoted nerve fiber regeneration and functional recovery, leading to an outcome comparable to median nerve repaired by autograft.